Trichomoniasis in Bothrops jararaca (serpentes, viperidae) - Vilela,F. C. (2003)
We describe a case of trichomoniasis in a Bothrops jararaca (Serpentes, Viperidae) donated to the Center for the Study of Venoms and Venomous Animals - CEVAP/UNESP. The animal had diarrhea with great quantity of flagellated protozoa in the feces. Microscopic examination of fecal smears stained with Giemsa revealed the presence of trichomonads, morphologically similar to Trichomonas acosta. Trichomonads were not detected in fecal exams after treatment with a single dose of 40 mg/kg metronidazole (Flagyl®).